Impact of induction therapy on outcomes after heart transplantation. Issue 10 (29th July 2021) - Tzani, Aspasia; Van den Eynde, Jef; Doulamis, Ilias P.; Kuno, Toshiki; Kampaktsis, Polydoros N.; Alvarez, Paulino; Briasoulis, Alexandros
Abstract: Background: Approximately 50% of heart transplant (HT) programs utilize induction therapy (IT) with interleukin‐2 receptor antagonists (IL2RA) or polyclonal anti‐thymocyte antibodies (ATG). Methods: Adult HT recipients were identified in the UNOS Registry between 2010 and 2020. We compared mortality between IT strategies with competing risk analysis. Results: A total of 28 634 HT recipients were included in the study (50.1% no IT, 21.3% ATG, 27.9% IL2RA, .7% alemtuzumab, .01% OKT3). Adjusted all‐cause, 30 day and 1 year mortality were lower among those treated with IT than no IT (sub‐hazard ratio [SHR] .87, 95% CI .79–.96, SHR .86, .76–.97, SHR .76, .63–.93, P = .007, respectively). In propensity score matching analysis IT was associated with lower 30‐day and 1‐year mortality. IL2RA had higher all‐cause and 1‐year mortality than ATG (SHR 1.41, 95% CI 1.23–1.69 and 1.55, 95% CI 1.29–1.88, respectively). Utilization of IT was associated with significantly lower risk of treated rejection at 1 year after HT compared with no IT (relative risk ratio [RRR] .79) and similarly ATG compared with IL2RA (RRR .51). Conclusion: IT was associated with lower mortality and treated rejection episodes than no IT. IL2RA is the most used IT approach but ATG has lower risk of treated rejection and mortality.